A Comparative Cost-Effectiveness Analysis of Percutaneous Transluminal Angioplasty With Optional Stenting and Femoropopliteal Bypass Surgery for Medium-Length TASC II B and C Femoropopliteal Lesions. (April 2019) - Vossen, Rianne J.; Philipszoon, Pilar C.; Vahl, Anco C.; Montauban van Swijndregt, Alexander D.; Leijdekkers, Vanessa J.; Balm, Ron
Purpose: To evaluate the total midterm costs and cost-effectiveness of percutaneous transluminal angioplasty with optional stenting (PTA/S) as initial treatment compared with femoropopliteal bypass (FPB) surgery in patients with medium-length TransAtlantic Inter-Society Consensus II (TASC) B and C femoropopliteal lesions.Materials and Methods: Over a period of 3 years, all hospital health care costs for 226 consecutive patients were calculated: 170 patients with a TASC B lesion and 56 patients with a TASC C lesion. In the 135-patient PTA/S group (mean age 69.9±10.9 years; 83 men), 108 (63.5%) patients had TASC B lesions and 27 (48.2%) patients had TASC C lesions. Ninety-one patients (mean age 68.4±10.9 years; 60 men) were treated with FPB for 62 TASC B and 29 TASC C femoropopliteal lesions. The main outcome measure was the primary patency rate at 3-year follow-up. Multiple imputation and bootstrapping techniques were used to analyze the data. The adjusted incremental cost-effectiveness ratios (ICERs) were calculated by dividing the difference in total costs by the difference in 3-year primary patency rate. Costs were expressed in euros (€), and cost differences are presented with the 95% confidence interval (CI).Results: Mean total costs per patient were €29, 058 in the PTA/S treatment group vs €42, 437 in the FPB group (mean adjusted difference –€14, 820, 95% CI –€29, 044 to −€5976). Differences in 3-year primary patency between PTA/S and FPB were small and nonsignificant (68.9% and 70.3%, respectively). An ICER of 563, 716 was found, indicating that FPB costs €563, 716 more per one extra patient reaching 3-year primary patency in comparison with PTA/S treatment.Conclusion: FPB in medium-length femoropopliteal lesions involved higher total costs when evaluated over a 3-year follow-up period. An endovascular-first approach is recommended, as this will result in cost minimization for patients with medium-length femoropopliteal disease.